EKSPLORASI ETNOMATEMATIKARUMAH ADAT SUKU LIO KABUPATEN ENDE UNTUK PEMBELAJARAN GEOMETRI - Maria Trisna Sero Wondo; Maria Fatima Mei; Finsensius Y. Naja (Unika Santu Paulus Ruteng, 2020)
This study aims to describe the symbols and geometry that exist in the traditional house of the Lio tribe of Wolokoli Village, Wolowaru District, Ende Regency in ethnomathematics perspective in terms of mathematical concepts. This type of research is qualitative research with an ethnographic approach. The subjects of this study consisted of several informants (chiefs, village heads, teachers and students). Using observation and interview techniques, and using qualitative descriptive analysis. The results showed the existence of symbol shapes and geometry in the building of traditional houses of the Lio tribe of Wolokoli Village, Wolowaru District, Ende Regency. Other symbolic forms include leke (foundation pillars made of stone and wood), there are twenty oval-shaped stone pillars and one rectangular wooden pole, Tenga (lante beam) in the form of a tube. Dalo is rectangular in shape. Rectangular lure. Wisu (four main pillars) shaped beam. Kebi (wall) is rectangular in shape. Mangu (nok pole) shaped beam. Block shaped jara. Pene / Pere is rectangular in shape. Eba beams. Lara is a block. Hubu (roof) is made of trapezoid-shaped reeds. Form symbols and geometrical structures that exist in the traditional Lio Tribe of Wolokoli Village, namely lines, angles, squares, rectangles, triangles, trapezoid, parallelogram, triangles, hexagons, beams, tubes, and triangular prisms. The shape in these parts of the house can change the paradigm of children and society that mathematics has a relationship with daily activities and relationships with culture and can be learned in a fun way in solving problems of learning geometry material.